Upah Muballigh Ditinjau Dari Hukum Islam (Kritik Atas Pemikiran Abdul Qadir Jawas) - Rizka Agustina Sikumbang, Khairul Bahri Nasution (Islamic Circle, 2023)
Abdul Qadir Jawas is one of the preachers whose opinions have recently sparked a lot of polemics among the public, especially his opinion about the prohibition of a preacher asking for wages from the congregation or organizers, because the preacher's wages are given by Allah SWT, even this action can be considered an act of shirk. The purpose of this study is to find out how Abdul Qadir Jawas views the wages of preachers and the views of Islamic law. The type of research used is library research on the thoughts of figures using content analysis techniques. Data is collected through videos and books. The results of the study concluded that according to Yazid Bin Abdul Qadir Jawaz, preachers should not ask for and expect wages from the congregation or organizers, because the preacher's wages are given by Allah SWT. According to him, he is not allowed to receive wages if the preacher is able to meet the needs of his family not through preaching even though the wages are given as a gift from the committee, he is not allowed to set rates for preaching, he is not allowed to enter into agreements regarding wages with the committee during preaching. Meanwhile in Islam, it is permissible to give or receive wages to preachers in preaching. The majority of scholars allow the preacher to receive compensation for the lectures or teaching of religious knowledge he gives as long as it is not the main goal.